How Mood Swings Affect Stock Markets: Looking at Footprints in social media - Badruddin, Syed Asad (Tufts Archival Research Center, 2005)
My research examines how mood swings affect stock markets, by tracking footprints of population moods on the social media mood aggregator called the Gross National Happiness Index of Facebook (GNH or gnh). I will be defining mood as the emotional state of the sample population. We will be checking for any correlation between the GNH and the Volatility Index (VIX), and the market premiums derived from the Capital Asset Pricing Model (CAPM) developed by Fama French. Stock market trends have the advantage that they are a reflection of economic activity updated daily, while other indicators such as GDP come out every quarter or every year.